Evaluation of optic nerve by histogram analysis on MRI in patients with isolated optic neuritis - Karaküçük, Seda Nida; Doğan, Adil; Baykara, Murat; Urfalıoglu, Selma (My University, 2023)
Objectives: We aimed to evaluate the Magnetic Resonance Imaging (MRI) histogram texture analyzis of the optic nerve by comparing patients of isolated optic neuritis with a healthy control group and to provide objective information without using contrast in the diagnosis of the disease. Methods: A total of 40 patients, including 20 patients with isolated optic neuritis (13 females, 7 males) and 20 healthy controls (11 females, 9 males), were included in the study. Non-contrast brain MR images of the patient and control groups were analyzed retrospectively. In the coronal T2-weighted MRI sequence of both groups, the Region of Interest (ROI) was placed in the extraocular anterior 1/3 of the optic nerve of both eyes. Numerical data were obtained using histogram analysis and the data were evaluated in the MATLAB program. The data were compared statistically. In addition, sensitivity and specificity were determined by Receiver Operating Characteristic (ROC) curve analysis. Results: As a result of histogram analysis, a significant difference was found between the mean values in the healthy and affected eye of the patients with isolated optic neuritis and the mean values of the control group (p < 0.05). A significant difference was found in standard deviation, minimum, maximum, median, variance values between both groups. ROC analysis was performed for mean value, AUC = 0.943 and when threshold value was selected as 354.258 Haunsfield Unit, two groups could be differentiated with 84.2% of sensitivity and 92.1% of specificity. We can say that patients with isolated optic neuritis also have histological effects on the clinically asymptomatic eye. Conclusions: Histogram analysis can be used in the diagnosis of the patients with isolated optic neuritis without the need to use contrast in their MRI. In addition, histological effect can be detected in the eye that does not show clinical symptoms with histogram analysis.
Keywords: Texture analysis; Optic neuritis; histogram analysis